Nowhere Near the Line : Pain and Possibility in Teaching and Writing - Boquet, Elizabeth, 1966- (Book collections on Project MUSE., 2016)
"Boquet traces the overlaps and intersections of a lifelong education around guns and violence, as a student, a teacher, a feminist, a daughter, a wife, a citizen, and across the dislocations and relocations that are part of a life lived in and around school"--Provided by publisher